2016
DOI: 10.1123/apaq.2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Dance Program on Static Balance on a Platform in Young Adults With Down Syndrome

Abstract: The purpose of the study was to compare postural control in static standing in young adults with and without Down syndrome (DS), with eyes closed and eyes open, before and after an 18-wk dance-based training program. The study included 11 young people with DS age 20.5 (1.3) yr and 11 without DS age 20.2 (2.0) yr. All parameters were recorded before and after the training program. Parameters related to center of pressure (COP; closed and open eyes) were recorded from a platform with the participant in bipedal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
1
21
0
1
Order By: Relevance
“…However, in adults with DS, walking may not be the best form of physical activity due to poor gait and stability challenges inherent to DS (Smith and Ulrich, , Agiovlasitis et al ., ) and could have been a contributing factor for the decrease in MVPA seen across time. Interventions that focus on functional movement and dance (Mcguire et al ., , Gutiérrez‐Vilahú et al ., , Ptomey et al ., ) have been found to be successful at increasing MVPA in adults with DS and should be included in future weight loss and physical activity interventions.…”
Section: Discussionmentioning
confidence: 96%
“…However, in adults with DS, walking may not be the best form of physical activity due to poor gait and stability challenges inherent to DS (Smith and Ulrich, , Agiovlasitis et al ., ) and could have been a contributing factor for the decrease in MVPA seen across time. Interventions that focus on functional movement and dance (Mcguire et al ., , Gutiérrez‐Vilahú et al ., , Ptomey et al ., ) have been found to be successful at increasing MVPA in adults with DS and should be included in future weight loss and physical activity interventions.…”
Section: Discussionmentioning
confidence: 96%
“…Other researchers have proposed dancing interventions such as ballet and choreography (Gutiérrez‐Vilahú et al . ) or traditional dance (Tsimaras et al . ), but they mainly focused on the effect that these kind of programmes had on the balance level of this population.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, all included studies trials demonstrated low risk except for three studies [5,17,24] that showed high risk.…”
Section: Allocation Concealmentmentioning
confidence: 96%
“…Only one study [24] out of eighteen showed a low risk of bias.…”
Section: Blinding Of Participants and Personnelmentioning
confidence: 97%
See 1 more Smart Citation